2005
DOI: 10.1242/jcs.01648
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-dependent interaction of lipid rafts with the actin cytoskeleton in activated human platelets

Abstract: IntroductionThe interactions between the plasma membrane and the cytoskeleton are essential for a wide variety of cellular processes such as endocytosis, cell morphology, cell adhesion, formation of cell-cell contacts and cell motility. These interactions are regulated by signaling complexes formed by the assembly of transmembrane and cytosolic proteins and lipids (Engqvist-Goldstein and Drubin, 2003;Fais and Malorni, 2003;Sechi and Wehland, 2000). These complexes are thought to participate in the control of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
60
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 55 publications
9
60
1
2
Order By: Relevance
“…In agreement with previous reports, 27,28 we found that pretreatment of platelets with a relatively high concentration (5mM) of M␤CD caused mild (Ͻ 20%) inhibition of thrombin induced aggregation, whereas there was no effect at lower M␤CD concentrations ( Figure 2A). In contrast, M␤CD caused a marked, concentration-dependent inhibition of rhodocytin-induced aggregation that reduced the response by greater than 95% at 5mM, with a partial effect observed at lower concentrations (1-2mM).…”
Section: Clec-2 Localizes To Lipid Rafts Upon Stimulation With Rhodocsupporting
confidence: 93%
“…In agreement with previous reports, 27,28 we found that pretreatment of platelets with a relatively high concentration (5mM) of M␤CD caused mild (Ͻ 20%) inhibition of thrombin induced aggregation, whereas there was no effect at lower M␤CD concentrations ( Figure 2A). In contrast, M␤CD caused a marked, concentration-dependent inhibition of rhodocytin-induced aggregation that reduced the response by greater than 95% at 5mM, with a partial effect observed at lower concentrations (1-2mM).…”
Section: Clec-2 Localizes To Lipid Rafts Upon Stimulation With Rhodocsupporting
confidence: 93%
“…Nevertheless, compared with JNK3 WT, an increase of JNK3 CS and a small decrease of JNK3 WT co-expressed with zD15 were detected at fraction 13, the high-density triton-insoluble fraction enriched with actinassociated cytoskeleton. 29 This implies that palmitoylation may affect JNK3's association with the actin cytoskeleton. Signals for actin cytoskeleton modulation are essential for axonal development.…”
Section: Resultsmentioning
confidence: 99%
“…Signals for actin cytoskeleton modulation are essential for axonal development. 30 To analyze this quantitatively, 29 we isolated the Triton-insoluble actin cytoskeleton fraction from cortical neurons and HEK293 cells expressing GFP-JNK3, followed by detection of JNK3. Consistently, JNK3 was detected in the Triton-insoluble fraction, which was sensitive to the actin depolymerizers cytochalasin D (Cyt.D) or latrunculin A (Lat.A) (Figure 3b).…”
Section: Resultsmentioning
confidence: 99%
“…29 Lipid rafts have been shown to be integral to platelet signaling pathways, 30 -33 and disruption of rafts is associated with reduced platelet activation. 30 We examined the effect of rHDL incubation on the binding of cholera toxin subunit B (CT-B) to the lipid raft marker ganglioside GM 1 on the surface of platelets. In resting platelets, rHDL was associated with a significant reduction in CT-B binding, suggesting reduced lipid raft assembly (77.3Ϯ1.3%; PϽ0.01).…”
Section: Mechanism Of Action: Rhdl Enhances Cholesterol Efflux and Rementioning
confidence: 99%